Estimation of Esomeprazole by RP-HPLC in Pure and Pharmaceutical Dosage Form - ROOSEWELT, C.; MAGESH, A.R.; RAVISUNDAR, A.; SHANMUGA PANDIAN, P.; MUTHUPRASANNA, P.; GUNASEKARAN, V. (Asian Journal of Chemistry, 2010)
A simple, precise RP-HPLC method was developed for the estimation of esomeprazole pure and pharmaceutical dosage forms. The quantification was carried out using C-18 column 250 × 4.6 mm i.d, 5 μm particle size in isocratic mode, with mobile phase comprising of buffer and acetonitrile in the ratio of 65:35 (v/v) pH 3.2. The flow rate was 1 mL/min and the detection was carried out by using UV detector at 295 nm. The retention time was found to be 6.30 min for esomeprazole. The method produced linear response in the concentration range of 200-1000 μg/mL for esomeprazole.The percentage recovery was found to be 99.98 %.The method was validated by evaluation of required parameters.